Philip Perry’s Manuscript Sketch of British History (c. 1770): Editing a Vallisoletan Historical Record of Early Britain - Carrera De La Red, Anunciación; Carrera De La Red, María José (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2019)
Sin resumen